Structural equation fit test of mathematical connection ability, mathematical reasoning, and mathematics problem-solving ability of junior high school students - Abdurrobbil Falaq Dwi Anggoro; Saleh Haji; Hari Sumardi (International Journal of Trends in Mathematics Education Research, 2022)
The purpose of this study was to test the compatibility of theoretical and empirical structural equations on the relationship between mathematical connection skills, mathematical reasoning, and mathematical problem-solving abilities of junior high school students. This is an ex-post facto research at SMP N 1 Bengkulu City. The population of this study was 296 people, and the sample was selected through a simple random technique of 100 people. Data collection techniques through tests with three research instruments. The three instruments are a mathematical problem-solving ability test, a mathematical reasoning ability test, and a mathematical connection ability test that have been valid and reliable based on expert tests and field tests. The data was tested using the Lisrel 8.8 application program. The results of the study are the P-valued of  0.05, RMSEA ≤ 0.08; NFI ≥ 0.90, NNFI ≥ 0.90; CFI ≥ 0.90; IFI ≥ 0.90; RFI ≥ 0.90; RMR ≤ 0.05; SRMR ≤ 0.05; GFI ≥ 0.90; and 0.8≤AGFI≤0.9; then the fit test for the complete structural equation model is good fit. It means that the theoretical structural equation model is compatible with the empirical structural equation model. Thus, the overall fit test of the model shows a fit model, and it can be concluded that the empirical structural equation model is compatible with the theoretical model.